Asymmetric Spinal Cord Compression by Intradural Extramedullary Tumor at Thoracic Level: A Case Report - Gavrila, Priska Gian; Dermoredjo, Sutaryanu (Acta Neurologica Indonesia, 2026)
Background: Spinal tumors are a rare type of tumor, accounting for approximately 15% of all tumors in the central nervous system. Most cases occur in individuals of working age. Symptoms may include localized pain or radiating pain to the extremities, and in some cases, severe motor deficits. Back pain tends to develop gradually, is independent of activity, and may worsen when lying down. CT scans, MRI, histopathological, and immunohistochemical examinations assist in establishing the diagnosis. The primary management of spinal tumors is surgical intervention, with the surgical approach varying depending on the type of tumor. Objective: To report the case of a 44-year-old female patient with a spinal tumor treated at Bethesda Hospital Yogyakarta. Case Description: A 44-year-old female presented with complaints of back pain lasting one month and bilateral lower extremity edema. In 2014, the patient experienced a fall in the bathroom resulting in loss of consciousness, and she undergoes spinal surgery in 2022. A non-contrast MRI revealed an intradural extramedullary mass at the level of thoracic vertebrae T2–T3, located on the left posterolateral aspect. Histopathological examination showed tumor tissue consistent with meningothelial and psammomatous meningioma, with a differential diagnosis of schwannoma. The patient undergoes a laminectomy as definitive management. Conclusion: Spinal tumors often present with pain and may result in severe motor deficits. Diagnosis is supported by imaging studies, histopathology, and immunohistochemistry to guide appropriate management.